Association of NRAMP 1 Gene Polymorphism with Susceptibility to Tuberculosis in Taiwanese Aboriginals - Yung-Hsiang Hsu; Chaio-Wei Chen; H. Sunny Sun; Ruwen Jou; Jen-Jyh Lee; Ih-Jen Su (Journal of the Formosan Medical Association, 2006)
The human homologue of mice natural-resistance-associated macrophage protein 1 (Nramp 1) gene, NRAMP 1, has been reported to play a role in susceptibility to tuberculosis in humans. The aboriginal population in Taiwan has a five-fold higher prevalence of tuberculosis than people of Han ethnicity. Whether genetic factors such as NRAMP 1 polymorphism play a role in the prevalence of tuberculosis in Taiwanese aboriginals should be clarified. Methods: NRAMP 1 polymorphism was studied using a case-control design of patients with tuberculosis, including subjects of Han (Hans) and aboriginal ethnicity in Hualien, eastern Taiwan. The polymorphisms of NRAMP 1 at loci INT4, D543N, 77-385C/T, 3-UTR (CAAA) deletion and 5-(CA)n microsatellite markers were assessed by polymerase chain reaction on tissue DNA isolated from 105 aborigines and 110 Hans with tuberculosis. Comparable numbers of ethnically-matched controls were studied simultaneously. Results: Two NRAMP 1 polymorphisms, INT4 and 5-(CA)n, were significantly associated with susceptibility to tuberculosis in aboriginals (p = 0.0070 and p = 0.0031, respectively). However, no association was detected at the five loci of NRAMP 1 polymorphisms among Hans (p > 0.08). Conclusion: Genetic variation in NRAMP 1 may affect susceptibility to and increase risk for tuberculosis in Taiwanese aboriginals. Although environmental factors play an important role in tuberculosis infection, genetic factors such as NRAMP 1 polymorphism may also contribute to the high prevalence of tuberculosis in Taiwanese aboriginals.